E-Preferred Approval Plan at a Large Academic Library: Assessment and Collection Development Implications. Issue 3 (3rd July 2018) - Tabacaru, Simona
Abstract: Academic libraries acquiring e-books through approval plans and other acquisition methods might question whether their collections are properly balanced between e-books and print books since patron needs vary across subject areas. This study examines seven years of monograph purchases at Texas A&M University Libraries (TAMU) through the approval plan vendor. Acquisition and use data are analyzed across subject areas. Study results inform how to balance print and e-collections to effectively support academic programs. TAMU purchased 78% of the monographs in print despite adopting an e-preferred approval plan, though most subject areas had higher e-book use compared to print.